Effectiveness of Baclofen in Detoxification of Opium Dependency, a Double-Blind Clinical Controlled Trial - Golnaz Feiz-Zadeh; Arash Mirab-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2003)
Objective: Results of some studies suggest that Baclofen (a GABA receptor agonist) maybe effective in detoxification of opium dependency. Thus we have done this study in order to identify possible efficacy of Baclofen for detoxification of opium dependency. Materials & Methods: This study is a double- blind randomized clinical trial. We selected 52 patients with opium dependency and with other criterias that we have designed on the basis of DSM-IV TR. Then we randomly assigned patients to two outpatient groups. The first group received Baclofen (40 mg/day) and second group received placebo for two weeks accompanied by similar drugs. The severity of the opium withdrawal symptoms was measured by SOWS (short opiate withdrawal scale) and two other questionnaires for measuring mental and physical symptoms of opium withdrawal in days of 0, 2, 4, 7 and 14. Results: Baclofen group showed superiority over placebo in the management of withdrawal symptoms of opium dependency, but there was not a significant statistical relationship. Conclusion: Baclofen maybe considered as an effective adjuvant agent in the management of mental and physical symptoms of opium withdrawal. However further studies to confirm our results are warranted.